Design, Synthesis, and Characterization of Multidentate Ligand Metal Complexes and their Evaluation as Corrosion Inhibitors in Acidic Media (Journal of the College of Basic Education, 2026)
This study systematically investigates the design, preparation, and activity of new bidentate, tridentate, and tetra dentate Schiff base ligands and their transition metal complexes as new advanced severe corrosion inhibiters for mild steel in acid media. We report the synthesis of three tetra dentate N₂O₂-donor Schiff base ligand containing various aromatic substituents (–OCH₃, –Cl, –H) by condensation reaction and their coordination to Cu(II), Ni(II) and Zn(II) ion to form neutral square-planar or octahedral complexes. Elemental analysis, FT-IR, UV-Vis spectroscopy, magnetic susceptibility, molar conductivity and thermogravimetric analysis were employed for the complete characterization of the compounds. The corrosion inhibition performance was evaluated using several methodsloss, potentiodynamic polarization (PDP) and electrochemical impedance spectroscopy (EIS) in 1M HCl.) Among them, the Cu(II) complex of the methoxy-substituted ligand (Cu–L₂) showed the most remarkable inhibition efficiency (94.7% at 5 mm, 25°C) and exhibited a mixed-type inhibition on both anodic and cathodic reaction. Adsorption fit to Langmuir isotherm model, with Gibbs free energy values (ΔGads ≈ −38.6 kJ/mol) indicating spontaneous, mixed physisorption and chemisorption process. DFT calculations confirmed that electron-donating moieties more favorably add electron density at donor atoms (N, O), thus decreasing the energy gap and promoting charge transfer to the metal surface. A complete inhibition mechanism is proposed wherein adsorption of the planar complex onto the steel surface takes place in a flat-lying manner providing a barrier against corrosive ions. A comparative analysis shows that the synthesized inhibitors are superior to or at least comparable to many of the newly published systems in terms of efficiency, thermal stability, and environmental friendliness. Our work defines a distinct structure–activity relationship as well as a promising avenue based on rational molecular design of multidentate ligand–metal complexes toward sustainable, high-efficiency anticorrosion solutions in industrial acid treatments.